A Review Of Recent Results on Cyclic Voltammetry Studies of Metal Chalcogenide Thin Films - Ho, Soon Min; Amala, Rani (UPM Press, 2018)
Cyclic voltammetric studies were done in an electrochemical bath to monitor the electrochemical reactions as described by many researchers. The study reviews recent results on cyclic voltammetry technique applied to the semiconductor thin films. All the voltammetry curves were scanned in the cathodic and anodic direction in order to find the optimum potential region where the formation of metal chalcogenide thin films. Ag/AgCI and saturated calomel electrode were used as reference electrode during experiment.